2015
DOI: 10.1039/c5cc03957f
|View full text |Cite|
|
Sign up to set email alerts
|

Effective Am(iii)/Eu(iii) separations using 2,6-bis(1,2,4-triazin-3-yl)pyridine (BTP) functionalised titania particles and hierarchically porous beads

Abstract: Hybrid materials which selectively extract Am(III) over Eu(III) from 0.01 M nitric acid solutions with fast kinetics and separation factors up to 160 have been synthesised. The materials consist of titania functionalised with a modified organic 2,6-bis(1,2,4-triazin-3-yl)pyridine (BTP) derivative. Both particles and hierarchically porous beads have been prepared and provide advantages over conventional solvent extraction separations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Replacing the current liquid-liquid extraction methods with a system based on a solid-phase extractant could eliminate the large volumes of secondary organic waste generated during separation. [24][25][26][27][28][29] To overcome the limitations of liquid-liquid extraction process, we previously demonstrated that when magnetic nanoparticles (MNPs) are combined with ligands such as CyMe 4 -BTPhen (2), these functionalized MNPs could be used to extract the minor actinides and the radioactive material could then be collected magnetically in preference to centrifugation. 30 In the present study, we report an alternative route for the synthesis of tetra(4-hydroxyphenyl)-BTPhen (10) as a highly effective reagent for carrying out actinide-lanthanide separations and investigate its extraction capabilities when immobilized on MNPs.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…Replacing the current liquid-liquid extraction methods with a system based on a solid-phase extractant could eliminate the large volumes of secondary organic waste generated during separation. [24][25][26][27][28][29] To overcome the limitations of liquid-liquid extraction process, we previously demonstrated that when magnetic nanoparticles (MNPs) are combined with ligands such as CyMe 4 -BTPhen (2), these functionalized MNPs could be used to extract the minor actinides and the radioactive material could then be collected magnetically in preference to centrifugation. 30 In the present study, we report an alternative route for the synthesis of tetra(4-hydroxyphenyl)-BTPhen (10) as a highly effective reagent for carrying out actinide-lanthanide separations and investigate its extraction capabilities when immobilized on MNPs.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…7,[13][14][15][16] Covering the period from 2013 onwards, the present review gives an update on BTP, BTBP, and BTPhen (Figure 1) compounds (including some promising modifications to the backbone) relating to An(III)/Ln(III) separations. We explicitly do not review the literature on solid-state structures, [17][18] solvent extraction process development, [19][20][21][22][23][24][25][26][27][28][29][30] solid-liquid applications, [31][32][33][34][35][36][37][38][39][40] radiolysis and stability studies, [41][42][43][44][45][46][47][48][49][50] non-An(III)-Ln(III) chemistry, [51][52][53][54][55][56] and theory studies. [57][58]…”
Section: Introductionmentioning
confidence: 99%
“…Needless to mention, the presence of such contaminated water in the form of three-quarters of our body can wreck havoc. , Of particular concern is the nonbiodegradable heavy metal ions such as Pb, Cd, or Hg, which can cause serious damage to the central nervous system, kidneys, and immune system of human beings once accumulated beyond a permissible concentration in the body. , Further corroborations come from some extensively publicized and well-documented massacres caused by water pollution-related diseases such as Minamata or itai-itai. , Naturally as a preventive measure, removal of such toxic metals from wastewater warrants remediation prior to their disposal in navigable waters or land. A number of techniques for wastewater treatments have been developed over the years including biological treatment, separation, ion-exchange, chemical and electrochemical techniques, and adsorption procedures. However, these processes suffer from several disadvantages, such as incomplete removal, high cost including costly regeneration processes, and high energy requirements . Therefore, development of cheaper and more effective methods to treat wastewater has become a matter of utmost importance in contemporary environmental research. , …”
Section: Introductionmentioning
confidence: 99%